2015
DOI: 10.2463/mrms.2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Imaging Parameters for Readout-segmented EPI of the Temporal Bone

Abstract: Readout-segmented echo planar imaging (rs-EPI) is a form of multi-shot EPI. rs-EPI is affected less by susceptibility artifacts than single-shot EPI (ss-EPI), which is widely used for diffusion-weighted imaging, so rs-EPI is expected to produce less image distortion. In this study, we compared rs-EPI and conventional ss-EPI of the temporal bone region, which contains abundant amounts of air and frequently exhibits changes in magnetic susceptibility. In addition, we used a phantom to determine the optimum rs-EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…11 So far, only a few studies have evaluated this new approach and found promising results. [17][18][19] This study evaluated RESOLVE-DWI for the detection of cholesteatoma and compared the results with surgical validation. Pooled sensitivity of non-EPI DWI for the detection of residual and recurrent cholesteatomas in a recent meta-analysis was 91% with a specificity of 92%.…”
Section: Discussionmentioning
confidence: 99%
“…11 So far, only a few studies have evaluated this new approach and found promising results. [17][18][19] This study evaluated RESOLVE-DWI for the detection of cholesteatoma and compared the results with surgical validation. Pooled sensitivity of non-EPI DWI for the detection of residual and recurrent cholesteatomas in a recent meta-analysis was 91% with a specificity of 92%.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative, recently introduced technique, which divides the k- space trajectory into multiple segments in the readout direction, limits susceptibility artifacts and geometric distortion. 1517 This so-called readout-segmented echo-planar DTI (rs-DTI) sequence uses multiple excitations followed by short echo-trains for the sampling of the tissue diffusion data, part by part, to then combine it to a final image. 15 Due to briefer echo-trains and shorter echo-spacing, in comparison to conventional ss-DTI sequences, rs-DTI is capable of achieving a higher image resolution, an increased signal-to-noise-ratio (SNR) and a reduction of susceptibility-based artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[14][15][16] An alternative technique is to divide the k-space trajectory into multiple segments along the readout direction (rs-DTI). [17][18][19] This requires multiple excitations followed by shorter echo trains, each of which only samples part of the raw data for a single image. The segmentation results in shorter minimum echo times, increasing the signal-to-noise ratio (SNR), and significantly reduces the severity of susceptibilityrelated artifacts.…”
mentioning
confidence: 99%